Bordering and Debordering Across Time. Refugees and Asylum Seekers Facing Chronopolitics - Della Puppa, Francesco; Storato, Giulia; Sanò, Giuliana (Italian Sociological Review, 2024)
With these contributes we investigate how refugees and asylum seekers deal with the politics of time that run within asylum policies, including the different production of temporal regimes along diverse types of migrant centres. By bringing together papers and case studies that map the trajectories of time undertaken by individuals in their daily routines and life experiences, we attempt to set up a reflection on the notion of a ‘landscape of time’. If, on the one hand, the interactions between spatial confinement and temporality of immigration controls realise multiple forms of (im)mobility of refugees and asylum seekers; on the other hand, the practices of routinisation, acceleration, stasis and waiting – exercised by individuals both inside and outside the centres and across the borders – can also be read as a tactic aimed at claiming time; a time which is differently experienced, according to the current system of social and civil stratification. Therefore, moving within these premises, we focus on how the ‘chronopolitics’ of the asylum and reception system affect daily lives and biographical trajectories of refugees and asylum seekers, both during their experience of migration and within the so called ‘reception system’.